Upaya Meningkatkan Minat Belajar Anak Melalui Bimbel Tunas Ceria Dukuh Krajan Desa Bedrug Pulung Ponorogo - Eny Novia Titriana; Teguh Ansori (Social Science Academic, 2023)
Interest in learning and lack of motivation are the main problems faced by students in the Krajan hamlet. In increasing interest in learning in the millennial era, where children are more interested in learning by using things that are interesting and relaxed.The service method used is Asset Based Community Development (ABCD). The result of this service activity is through the program Learning while playing in the learning process, children's interest and enthusiasm for learning. Thus, it is hoped that children will not feel that they are learning, thus making learning activities relaxed, flexible and not rigid. The purpose of this research was to increase children's learning interest and to find out the extent to which students' motivation was in learning outside of school. The collaborative use of these four learning methods was quite significant in conveying material.The krajan hamlet of Bedrug Village is located in the Pulung sub-district, Ponorogo Regency. In general, the education of the people of Bedrug Village can be categorized based on age. The elderly have the last elementary school (SD) and junior high school (SMP) education. Meanwhile, in adulthood, the average last education is Senior High School/Equivalent (SMA) and Strata-1 (S-1).